Coping Strategies for Mothers Working as Inpatient Nurses in Hospitals - Eriska Amy Maulita; Ririn Isma Sundari; Arni Nur Rahmawati (Journal Keperawatan, 2026)
Background: Female nurses working in inpatient settings face significant responsibilities at work and in their families. Work demands, dual roles, and emotional pressure can cause stress, affecting psychological well-being, burnout risk, work quality, and nursing care quality. Coping strategies are one way nurses manage stress while fulfilling their roles as mothers and healthcare workers. Purpose: To describe the level of coping strategies and dominant types of coping used by mothers who work as inpatient nurses at Dr. R. Goeteng Taroenadibrata Purbalingga Regional General Hospital. Methods: The study used a quantitative descriptive design with a cross-sectional approach. The study population consisted of 78 female nurses in inpatient settings, with a sample of 65 respondents selected using a purposive sampling technique. Inclusion criteria included female nurses who were married, had children, and worked in inpatient settings. Data were collected using the Brief COPE questionnaire and analyzed univariately using frequency distribution and percentages. Results: The research results showed that the majority of respondents (45, or 69.2%) used moderate coping strategies. Meanwhile, the most commonly used coping strategy among nurses was problem-focused coping, with 45 respondents (69.2%), suggesting that they tended to solve problems directly when facing stress. Conclusion: Most mothers working as inpatient nurses have moderate coping strategies, with a predominance of problem-focused coping strategies. These results indicate the need to strengthen adaptive coping strategies through psychological support programs, stress management training, and increased social support in hospitals, especially for maternal nurses.